A leitura literária: uma análise do ensino do 7º ano na escola Perciliano Tourão em Igarapé - Miri-PA - GONÇALVES, Cláudia Maria da Cunha (2019)
The present work was developed from the research done during the internship at a municipal institution of basic and elementary education in the municipality of Igarapé-Miri in the State of Pará, where we analyzed how the process of utilization of literary reading in education to the 7th grade students at the Perciliano Tourão School in Igarapé-Miri / PA. The research aimed to analyze how teachers of elementary school work with literary teaching in the classroom, and how the process of meaning of the experiences lived by students in their daily life from the literary practice worked by the teaching institution. Among the main findings of this research is the literary reading that enhances learning by promoting the widening of the individual and collective horizons in the social and cultural spheres, guaranteeing a critical and emancipatory formation. In that practice is important so that students can perceive literary reading as an instrument of pleasure, allowing them to explore other contexts, other people, other ideas, and, thus, can interact in the society in which they are inserted.